Enzymatic properties of CARF-domain proteins in Synechocystis sp. PCC 6803 - Ding, Jin; Schuergers, Nils; Baehre, Heike; Wilde, Annegret (Frontiers in Microbiology, 2022)
Prokaryotic CRISPR-Cas systems provide immunity against invading genetic elements such as bacteriophages and plasmids. In type III CRISPR systems, the recognition of target RNA leads to the synthesis of cyclic oligoadenylate (cOA) second messengers that activate ancillary effector proteins via their CARF domains. Commonly, these are ribonucleases (RNases) that unspecifically degrade both invader and host RNA. To mitigate adverse effects on cell growth, ring nucleases can degrade extant cOAs to switch off ancillary nucleases. Here we show that cyanobacteria harbor functional CARF-domain effector and ring nuclease proteins. We purified and characterized the two ancillary CARF-domain proteins from the III-D type CRISPR system of the model organism Synechocystis sp. PCC 6803. The Csx1 homolog, SyCsx1, is a cyclic tetraadenylate(cA4)-dependent RNase with a strict specificity for cytosine nucleotides. The second CARF-domain protein with similarity to Csm6 effectors, SyCsm6, did not show RNase activity in vitro but was able to break down cOAs and attenuate SyCsx1 RNase activity. Our data suggest that the CRISPR systems in Synechocystis confer a multilayered cA4-mediated defense mechanism.